Pengaruh Tata Kelola Perusahaan dan Kualitas Laporan Tahunan terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2017) - Inovesia Munthe; Aditya Septiani (Diponegoro Journal of Accounting, 2020)
The purpose of this paper is to investigate whether the corporate governance practices and the quality of financial reporting are associated with the firm value for manufacture firms in Indonesia. Characteristics of the corporate governance and the quality of financial reporting as an independent variable. Firm value as a dependent variable was measured by using market to book value ratio (PBV). And size, leverage and growth of firms as the control variables. The sample in this research is manufacturing companies in Indonesia Stock Exchange during period 2016-2017. The sampling method in this research is purposive sampling. This research hypothesis were there are positive associations between firm value and corporate governance practices and reporting quality. The corporate governance was measured by Corporate Governance Index (CGI) which the regulations was issued by Otoritas Jasa Keuangan (OJK) with regulations number 32/SEOJK.04/2015. Second, the reporting quality was measured by Reporting Quality Index (RQI) which the regulations was issued by Otoritas Jasa Keuangan (OJK) with regulations number KEP-431/BL/2012. To examines the associations, the analysis technique is by using Ordinary Least Square (OLS) regressions for firm value on the two indices. The final findings of this research are the paper finds positive associations between corporate governance and firm value. These findings suggest that firms that implement better corporate governance have higher values. Contrary with the second hypothesis, the paper finds negative associations between reporting quality and firm value. These findings indicate that firms with lower value tend to disclose more information that is consistent with OJK than firms with higher value.